SEXUALIDADE E REPRODUÇÃO COMO DIREITOS DAS PESSOAS COM DEFICIÊNCIA INTELECTUAL E SUAS INTERFACES COM AS POLÍTICAS PÚBLICAS NACIONAIS DE EDUCAÇÃO E SAÚDE: lacunas e possibilidades - Renato Barboza (Universidade Federal do Maranhão, 2013)
The present article discusses the public policies of the Education and Health that are in development in the country for the people with intellectual disabilities in the context of sexual and re- productive rights, from the problem of STD/AIDS. It examines the issue of social inclusion under the Convention on the Rights of Persons with Disabilities of the United Nations Organization, ratified in Brazil in 2008, and other official documents of public policy in the country, to reducing vulnerabilities in this population. It discusses the concept of vulnerability and analyzes the individual, social and programmatic dimensions, about the advances and challenges in the implementation of effective social policies and social programs in these sectors in the contemporary scenario.